EFFECT OF DIETARY SUPPLEMENTATIONS ON BODY CONDITION SCORE, OCCURRENCE OF POST PARTURIENT DYSGALACTIA SYNDROME, LITTER PERFORMANCE AND SERUM BIOCHEMICAL PROFILE IN TRANSITION SOWS - PATRA, MANAS KUMAR; KUMAR DE, UJJWAL; KENT, YHUNTILO; RUNGSUNG, SOYA (The Indian Journal of Animal Reproduction, 2021)
The aim of the present study was to investigate the effect of different dietary supplementations in periparturient sow diet on the occurrence of post parturient dysgalactia syndrome (PDS), body condition score (BCS), litter performance and serum biochemical profile. Forty-eight pregnant multiparous crossbred sows (Hampshire × Ghungroo) were randomly divided into four groups (12 sows per group) 30 days before expected date of farrowing as control (Basal diet); probiotics (Basal diet + Probiotics); Vitamin E-selenium and aminoacids (Basal diet + VES-AA) and calcium-vitamin (Basal diet + Cal-Vit). The results of the study revealed that the occurrence of PDS was lowest (p<0.05) in VES-AA than the Probiotic and Cal-Vit mix groups. The incidence of still birth and piglet scour were significantly lower (p<0.05) in VES-AA and Cal-Vit mix groups as compared to probiotic and control groups. A significantly lower (p<0.05) incidence of piglet mortality was noted in VES-AA group than and probiotic, Cal-Vit mix and control groups. The mean BCS was significantly decreased (p<0.05) on day 15 and 45 after farrowing than the value of day -15 in all the groups and the mean BCS was significantly higher (p<0.05) on day 45 in probiotic, VES-AA, Cal-Vit mix than control group. The piglet performance and weaning to estrus interval sows were not affected across the groups. Similarly, mean serum biochemical parameters did not alter throughout the study period in all the groups. From the findings of the present study, it is concluded that the dietary vitamin E- selenium along with amino acid supplementations from late gestation to throughout lactation could contribute, at least in part, to decrease the occurrence of PDS of sow, incidence of still birth, piglet scour and mortality.